The L2 motivational self system: A meta-analysis - Al-Hoorie, Ali H. (Studies in Second Language Learning and Teaching, 2018)
This article reports the first meta-analysis of the L2 motivational self system (Dörnyei, 2005, 2009). A total of 32 research reports, involving 39 unique samples and 32,078 language learners, were meta-analyzed. The results showed that the three components of the L2 motivational self system (the ideal L2 self, the ought-to L2 self, and the L2 learning experience) were significant predictors of subjective intended effort (rs = .61, .38, and .41, respectively), though weaker predictors of objective measures of achievement (rs = .20, -.05, and .17). Substantial heterogeneity was also observed in most of these correlations. The results also suggest that the strong correlation between the L2 learning experience and intended effort reported in the literature is, due to substantial wording overlap, partly an artifact of lack of discriminant validity between these two scales. Implications of these results and directions for future research are discussed.